Factors Affecting University Students’ Intention to Invest in Cryptocurrency as a Digital Investment Instrument - Alif Lam Ra; Rayna Kartika (Jurnal Economia, 2026)
The study seeks to empirically demonstrate the mediating role of investment knowledge, alongside return, risk, influencer, ease of use, and gender as exogenous variables, in the relationship between these variables and the intention to invest, which is treated as endogenous. This study used purposive sampling. A total of 702 respondents, comprising university students, participated in the study. Data analysis was conducted using SEM-PLS. The findings indicate that investment knowledge, return, risk, influencer, and ease of use positively influence the intention to invest. Additionally, investment knowledge exhibits a modest mediating effect on the relationship between return and risk concerning investment intentions. Furthermore, investment knowledge partially mediates the influence of return and risk on the intention to invest in cryptocurrencies. Conversely, gender demonstrates a negative effect on investment intention. These results suggest that higher levels of investment knowledge, returns, risk, influencer impact, and ease of use are associated with a greater likelihood of investing in cryptocurrency.